2021
DOI: 10.1186/s13054-021-03772-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tight glucose control on circulating 3-hydroxybutyrate in critically ill patients

Abstract: Background Recent evidence suggests a potentially protective effect of increasing ketone body availability via accepting low macronutrient intake early after onset of critical illness. The impact of blood glucose control with insulin on circulating ketones is unclear. Whereas lowering blood glucose may activate ketogenesis, high insulin concentrations may have the opposite effect. We hypothesized that the previously reported protective effects of tight glucose control in critically ill patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Propofol infusion in TBI patients with KD should be considered carefully due to risk of propofol infusion syndrome and calories needs to be adjusted. In our study, we have safely administered propofol with ketogenic diet and similar results were produced by Bui et al [43] when propofol was given in brief and small infusion [42]. Intensive insulin therapy to lower glucose level, which in turn can cause ketogenesis and raises ketone bodies and BHB concentration.…”
Section: Strategies To Modulate Beta-hydroxybutyratesupporting
confidence: 75%
See 1 more Smart Citation
“…Propofol infusion in TBI patients with KD should be considered carefully due to risk of propofol infusion syndrome and calories needs to be adjusted. In our study, we have safely administered propofol with ketogenic diet and similar results were produced by Bui et al [43] when propofol was given in brief and small infusion [42]. Intensive insulin therapy to lower glucose level, which in turn can cause ketogenesis and raises ketone bodies and BHB concentration.…”
Section: Strategies To Modulate Beta-hydroxybutyratesupporting
confidence: 75%
“…Study analysis suggested that tight or liberal glucose control does not affect the BHB concentration in critically ill patients. Therefore, insulin may not offer any additional benefits to such patients [43]. Overall, a ketogenic diet is a more physiological way of inducing ketosis.…”
Section: Strategies To Modulate Beta-hydroxybutyratementioning
confidence: 99%
“…Mechanistic studies have attributed harm by severe iatrogenic hyperglycemia to glucose overload in vital organs, and not to lack of insulin effect [78]. Indeed, insulin by itself may have unwanted side effects on organ recovery, as insulin is a powerful suppressor of autophagy and ketogenesis [79,80]. This may explain why lower glucose levels independently associated with improved outcome in RCTs, whereas increased insulin doses independently associated with harm [81].…”
Section: Mechanisms Explaining Lack Of Benefit Of Early High-dose Nut...mentioning
confidence: 99%
“…In the PEPaNIC RCT, the majority of hypoglycemic events occurred in patients not receiving early PN, and the glucose control protocol varied per center, going from tight over intermediate to liberal glucose control [ 10 ]. Different feeding and glucose control strategies have a different risk of iatrogenic hypoglycemia and may variably affect generation of ketone bodies that are vital alternative substrates for the brain during hypoglycemia [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%